An Exploration of Professional Learning for Chief Diversity Officers in Higher Education - Robert G. Bryant; Talmadge Guy (Adult Education Research Conference, 2014)
The purpose of the study is to understand the process of professional learning of Chief Diversity Officers (CDOs) who work in higher education. Professionals who become CDOs come from a variety of backgrounds and rely on professional experiences, along with “on-the-job” learning rather than pre-service education to navigate the role of a diversity executive. Cervero (2001) stated the importance of continued professional education to continue learning so that individuals develop and enhance their practice. Professional learning is important for diversity executives who are in higher education because there is no pre-service formal education program, and the profession is still developing a common body of knowledge. For this study, professional learning is framed as a combination of continuing professional education, the context of work, and individual experiences. Daley (2000) supports the combination of the three areas to have optimal learning in professions. This roundtable discussion is a discussion about a study conducted to explore the process of professional learning for CDOs working in higher education institutions. At the core of the study is the process of learning as professionals function as a diversity executive.